If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(x+7)=4x-4+2(4x+3)
We move all terms to the left:
-2(x+7)-(4x-4+2(4x+3))=0
We multiply parentheses
-2x-(4x-4+2(4x+3))-14=0
We calculate terms in parentheses: -(4x-4+2(4x+3)), so:We get rid of parentheses
4x-4+2(4x+3)
determiningTheFunctionDomain 4x+2(4x+3)-4
We multiply parentheses
4x+8x+6-4
We add all the numbers together, and all the variables
12x+2
Back to the equation:
-(12x+2)
-2x-12x-2-14=0
We add all the numbers together, and all the variables
-14x-16=0
We move all terms containing x to the left, all other terms to the right
-14x=16
x=16/-14
x=-1+1/7
| 5x/x³+5=5/x³-7 | | 8.6+0.9x=14.8 | | -2(4m-1)=-5(7m+5) | | 3m+14=+5 | | (b^2)=-6-7b | | 2(2a+1)=8+4a | | v/8− 1=2 | | -8(n-2)=-10+5n | | .4(−3−6a)=36 | | 3(2x−5)−4x+8=−1 | | 4/5=r/2.5 | | -0.7(5x+3)=-3x-9 | | 8+6x=15x-1 | | 8+2t=26 | | -13c-10c-8c+6c+19c=-6 | | -5(-3r-3)=75 | | n²+n=132 | | 4(−3−6a)=36 | | (x)=4x+5(-8) | | 3x×78=81 | | 16r-11r-r=16 | | 6(x-1)=−72 | | -3n+18+7n=58 | | -12x-6=3x-6 | | (2t-1)/3=(3t+2)/15 | | 9(x-1)-9=6x+3(-5+x) | | 6x+7=-6+4x+21 | | -31=3v+9-8v= | | 1/5x=85 | | x2/3=90 | | 11.2d-12.72=13.6d | | -5(3x-3)+9x=6(x+4) |